PREREQUISITES FOR DEVELOPMENT OF STRATEGIES FOR CORRECTION AND PREVENTION OF POSTURAL DISORDERS IN YOUNG BASKETBALL PLAYERS - Nevolin , D. A. (Rehabilitation and Recreation, 2023)
The aim of the article is to determine the prerequisites for developing a strategy for correction and prevention of postural disorders in young basketball players. Research methods include theoretical analysis of special literature sources, method of pedagogical observation. The data received as a result of scientific and methodological literature sources analysis as well as monitoring Internet sources gave us the opportunity to present main theses concerning prerequisites of designing strategy for correction and prevention of postural disorders in young basketball players. In particular, changes in musculoskeletal system of basketball players at the initial stage of their training are mainly due to the development long muscles, which determine speed and flexibility of movements; regarding children of this period of ontogenesis, the muscles of the upper and lower limbs are well developed, in contrast to the muscles of the back and trunk, which are not yet able to maintain the body in the necessary position for a long time or keep the spine in a stable position, which in its turn can lead to posture disorders. Strength of muscles, their uniform development, the distribution of muscle thrust and the uniform work of all muscles, which will allow maintaining the correct posture, are important for formation of young basketball players’ posture. Long-term process of athletes’ training in basketball affects the state of their musculoskeletal system, changing the physiological process of posture formation to pathological adaptation, which is reflected in changes of individual biolinks position in both sagittal and frontal planes. The main variables in emergence of posture disorders in basketball players are age, which determines projection the shoulder girdle alignment and shoulder blades position, height, the letter determines asymmetry of the shoulder blades, and dominance of the leading hand affects the lumbar kyphosis. Many years of playing basketball can lead to an increase in asymmetry of body posture, which is most often manifested not only in an increase in asymmetry of the pelvis location in transverse plane, asymmetry of shoulder blades relative to transverse plane and a decrease in thoracic kyphosis angle, but also in a line deviation of spinous processes, a change in the angle of trunk leaning, a violation of shoulder blades location norms in the transverse plane and to the spine, etc. Thus, the issue of targeted correction and prevention of musculoskeletal system disorders in young basketball players at the initial stages of their long-term training has not been sufficiently investigated. The basic components of author's strategy include conceptual foundations of 9–10-year-old basketball players’ training at the stage of their initial training (2nd year of their training); theoretical and methodological approaches to correction and prevention of posture disorders in young athletes. The systematized provisions of prerequisites of strategy for correction and prevention of postural disorders in young basketball players and theses content highlighted by us emphasize the need to consider basketball not only as a means of emotional addition to other corrective and preventive methods, but also to consider this sport as a completely independent therapeutic unit for effective use of which it is necessary to carry out a scientifically based and practically proven integration into educational and training process.